2021
DOI: 10.1101/2021.09.06.459109
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of directionality and efficiency of the ATP synthase Fo motor at atomic resolution

Abstract: Fo subcomplex of ATP synthase is an membrane-embedded rotary motor that converts proton motive force into mechanical energy. Despite a rapid increase in the number of high-resolution structures, the mechanism of tight coupling between proton transport and motion of the rotary c-ring remains elusive. Here, using extensive all-atom free energy simulations, we show how the motor's directionality naturally arises from the interplay between intra-protein interactions and energetics of protonation of the c-ring. Not… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Directionality is not the only important factor to consider in molecular ratchet design. [24][25][26][27][28][29]31 The rate of the machinecatalyzed fuel-to-waste reaction determines how fast a motor can operate. 1,31,33,36 Here also, EDC•MeI was the preferable carbodiimide fuel as it reacts faster, which combined with the better directionality means that the ratchet undergoes net forward chemomechanical cycles at over double the rate with EDC•MeI compared to that with DIC or DCC (Figure 4C).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Directionality is not the only important factor to consider in molecular ratchet design. [24][25][26][27][28][29]31 The rate of the machinecatalyzed fuel-to-waste reaction determines how fast a motor can operate. 1,31,33,36 Here also, EDC•MeI was the preferable carbodiimide fuel as it reacts faster, which combined with the better directionality means that the ratchet undergoes net forward chemomechanical cycles at over double the rate with EDC•MeI compared to that with DIC or DCC (Figure 4C).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For example, diesel engines need to produce substantial torque to pull heavy loads, while gasoline engines are generally designed to maximize speed and/or efficiency. 23 Features of biomolecular machines have evolved to similarly suit their functions: 24−27 to transport cargo, 28,29 a motor needs to be fast to beat diffusion, while the external force it can successfully pull against is less important. Conversely, speed of operation is less consequential for motor proteins in muscle cells, 11,30 while the force they can exert is the primary requirement.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, all-atom free energy calculations of ScF O found independent evidence of the 11° sub-step (Marciniak et al, 2022), confirmed that the differences in pKa values bias c-ring rotation in the synthase direction, and revealed similar energetic contributions from desolvation energies and electrostatic interactions to that observed from our singlemolecule studies (Yanagisawa and Frasch, 2021). In addition, Marciniak et al (2022) found that the yeast equivalent of aR210 (aR176) dictates the direction of rotation, controls the protonation state of the proton-release site, and separates the two input and output channels. As a result, this arginine is necessary to avoid slippage between proton flux and the mechanical output to guarantee highly efficient energy conversion.…”
Section: Step-2 the 25° Sub-step Is Powered By Electrostatic Attracti...mentioning
confidence: 99%